The impact of self-selection based on HIV risk on the cost-effectiveness of preexposure prophylaxis in South Africa. (1st May 2020) - Jamieson, Lise; Gomez, Gabriela B.; Rebe, Kevin; Brown, Ben; Subedar, Hasina; Jenkins, Sarah; Shoko, Natsai; Bekker, Linda-Gail; Johnson, Leigh F.; Meyer-Rath, Gesine
Abstract : Objectives: We explored the impact and cost-effectiveness of preexposure prophylaxis (PrEP) provision to different populations in South Africa, with and without effective self-selection by individuals at highest risk of contracting HIV (through concurrent partnerships and/or commercial sex). Design and methods: We used a previously developed HIV transmission model to analyse the epidemiological impact of PrEP provision to adolescents, young adults, pregnant women, female sex workers (FSWs) and (MSM), and data from South African PrEP programmes to estimate the cost and cost-effectiveness of PrEP (cost in 2019 USD per HIV infection averted over 20 years, 2019, 38). PrEP uptake followed data from early implementation sites, scaled-up linearly over 3 years, with target coverage set to 18% for adolescents, young adults and pregnant women, 30% for FSW and 54% for MSM. Results: The annual cost of PrEP provision ranges between $75 and $134 per person. PrEP provision adolescents and young adults, regardless of risk behaviour, will each avert 3.2--4.8% of HIV infections over 20 years; provision to high-risk individuals only has similar impact at lower total cost. The incremental cost per HIV infection averted is lower in high-risk vs. all-risk sub-populations within female adolescents ($507 vs. $4537), male adolescents ($2108 vs. $5637), young women ($1592 vs. $10 323) and young men ($2605 vs. $7715), becoming cost saving within 20 years for high-risk adolescents, young women, MSM and FSWs. Conclusion: PrEP is an expensive prevention intervention but uptake by those at the highest risk of HIV infection will make it more cost-effective, and cost-saving after 14–18 years. Abstract : Supplemental Digital Content is available in the text